Describing the health behaviours of future nurses: a cross-sectional study among Italian nursing students: Health behaviors in nursing students - Arrigoni, Cristina; Grugnetti, Anna Maria; Caruso, Rosario; Dellafiore, Federica; Borelli, Paola; Cenzi, Maria; Gallotti, Luisa; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
Academic environments may influence the achievement of healthy behaviors in nursing students. However, the lifestyles among Italian nursing students have been poorly investigated. Therefore, the aim of this study was to describe the health behaviours of Italian undergraduate nursing students. A monocentric, cross-sectional, study design was performed. The study was conducted in an undergraduate nursing course in the north of Italy (University of Pavia). Data were collected through the list of freshmen in nursing in March 2018 (i.e. first years of the undergraduate program) using an online survey and a purposive sampling, where 134 nursing students were enrolled. The results highlighted that the nursing students observed a varied and balanced alimentation. The most problematic areas are referred to the physical activity and the smoking habits. Future research should frame the trajectory of the undergraduate nursing students over the overall education path, also promoting and testing strategies to address the observed issues, such as limited physical activities and smoking habits.